PEMBELAJARAN ETNOSAINS BERVISI SETS UNTUK MENINGKATKAN KETERAMPILAN PROSES SISWA - Henry J Saputra (Universitas PGRI Yogyakarta, 2016)
Learning is a process organized by teachers to membelajarkan students in learning acquire and process knowledge, skills, and attitudes. In general, learning is defined as the process of individual behavior change as a result of interaction with the environment. So the change in behavior is the result of the study, which means that a person is said to have learned if he can do something that can not be done before. Conceptual learning activities should be close to the environment. Therefore, learning activities should make optimum use of the potential of the environment to make it more meaningful. Potential local environment, especially the local culture, is not utilized optimally teacher in the learning process. Learning tend to give priority to the development of the intellectual aspects of the textbook grip teacher becomes the main source of learning. With a vision of learning activities etnosains this SETS students will learn not conceptually but is associated with the habit or culture of the people around so it can be used to explain the scientific culture that flourished in the environment. Through a contextual approach and SETS (Science Environmental Tecnology and society) is able to provide assistance to teachers in the link between what is taught with real-world situations students and encourage students to make connections between the knowledge possessed by its application in everyday life -day.